Comparison of first and fourth-year nursing students in terms of their knowledge on methods for preventing infectious diseases - Ozguler, Muge; Bulut, Aliye; Celik, Gulay (Annals of Medical Research, 2021)
Aim: The purpose of this study is to compare the first- and fourth-year nursing students in terms of their knowledge on methods for preventing infectious diseases. Material and Methods: While the population of the study was composed of 143 students studying in the first and fourth years of the Nursing Department in Bingol University Faculty of Health Sciences, the sample of the study consisted of 117 students who supported the implementation of the study and were voluntary to participate in the study (Response rate: 81.8%).Results: When the responses of the first and fourth-year students were compared in 3 of the items given about the definition and characteristics of infectious diseases, the difference between them was found to be significant (p0.05). When the answers of the first- and fourth-year students were compared in 5 of the 6 items given about sexually transmitted infections. The difference between them was found to be significant (p0.05). In all items, the percentage of giving correct answer was higher in fourth-year students compared to the first-year students. Conclusions: It was observed in the present study that general knowledge levels of the nursing students about infectious diseases and their knowledge levels about Sexually Transmitted Infections were not sufficient. When the knowledge levels of the first-year students were compared with those of the senior students, it was determined that the knowledge levels increased with education, but it was still not sufficient.
Keywords: Infectious diseases; knowledge level; nursing students; sexually transmitted infections